Strategic financial management for small and medium sized companies - Karadag, Hande (United Kingdom : Emerald, 2015)
This book serves as a guide to prevent small business owners and novice entrepreneurs from experiencing financial disasters. Research shows a majority of small businesses fail in their early years due to poor financial management, turning the dreams of many business owner and novice entrepreneur into nightmares.
1. Introduction -- 2. An outlook of small and medium sized enterprise -- 3. A strategic management approach to financial management -- 4. Strategic financial planning and forecasting in small and medium sized business -- 5. Strategic working capital management in small and medium sized business -- 6. Strategic capital structure management in small and medium sized business -- 7. Strategic fixed-asset management in small and medium sized business -- 8. Strategic international trade financing in small and medium sized business -- 9. Strategic financial reporting and control in small and medium sized business -- 10. Conclusion .
Includes bibliographical references and index.
Keywords: SMALL BUSINESS; BUSINESS AND ECONOMICS